Ignition Process and Flame Lift-Off Characteristics of dimethyl ether (DME) Reacting Spray - Cung, Khanh Duc; Moiz, Ahmed Abdul; Zhu, Xiucheng; Lee, Seong-Young (Frontiers in Mechanical Engineering, 2021)
Advanced combustion systems that utilize different combustion modes and alternative fuels have been known to show significant improvements in combustion performance and emissions as compared to conventional diesel or spark-ignited combustions. As an alternative fuel, Dimethyl ether (DME) has been receiving much attention as it can be run effectively under low temperature combustion (LTC) modes such as homogeneous charge compression ignition (HCCI) and reactivity control combustion ignition (RCCI). Under compression-ignition (CI), DME can be injected as liquid fuel into a hot chamber, resulting in a diesel-like spray/combustion characteristic. With its high fuel reactivity and unique chemical formula, DME ignites easily, but produces almost smokeless combustion. In the current study, DME spray combustion under several different conditions of ambient temperature (Tamb = 750-1100 K), ambient density (ρamb = 14.8-30 kg/m3), oxygen concentration (O2 = 15-21%), and injection pressure (Pinj = 75-150 MPa) were studied. Results from both experiment (constant-volume combustion vessel) and numerical simulations were used to develop empirical correlations for ignition and lift-off length. Compared to diesel, the established correlation of DME shows a similar Arrhenius-type expression. Sensitivity studies shows that Tamb and Pinj have stronger effect on ignition and combustion of DME rather than other parameters. Finally, this study provides a simplified conceptual mechanism of DME reacting spray under both high reactivity ambient (high Tamb, high O2) and LTC conditions. Some perspective has been given on engine operating strategies using a non-conventional fuel such as DME with different reactivity and chemical property.